Middle Eastern Christians facing challenges: reflections on the special Synod for the Middle East - Winkler, Dietmar W. (Pro Oriente studies in the Syriac tradition, 2019)
"In 2010, the "Middle East Synod" took place in Rome. It was a milestone for Middle Eastern Christianity charged with hopes for the challenged churches in their difficult situations in the midst of a region in radical change. The PRO ORIENTE Foundation (Vienna/Austria), in its effort to promote dialogue and ecumenical relations, accompanied the Synod with a preceding study seminar in Sulaymaniah (Iraq) and with its third Colloquium Syriacum in Vienna as a contribution of its reception process. Thus, the main focus of the articles of the present volume is on "relations", i.e. on Christians and Churches within their socio-political, religious and ecclesial environments. This means that ecumenical relations and communion are at stake as well as relationships, witness and dialogue with Jews, Muslims and the respective states as well as new relations in the West, because of emigration and diaspora. The book includes contributions by Cardinal Christoph Schönborn and Cardinal Kurt Koch, Cardinal Louis Raphael I Sako, Patriarch Ignatius Youssef III Younan, Archbishops Basilios Georges Casmoussa, Mar Gregorios Yohanna Ibrahim, Paul Nabil El-Sayah and Boulos Matar as well as Frans Bouwen MAfr, David Mark Neuhaus SJ, Herman G.B. Teule, and Dietmar W. Winkler"--